Leadership Competencies: a School Leader Evaluation - Isnada Waris Tasrim; Mahfud M Gamar (Postgraduate Program Magister Pendidikan Agama Islam, 2022)
This study aimed at examining how teachers evaluate their principal’s leadership competencies in terms of principal-staff relation, organization, and building management, student relationship, curriculum and program development, community, and parent relation. This descriptive qualitative research was conducted at elementary and middle schools. The subjects were 30 teachers. The data were gathered using the Performance Evaluation of Education Leader. The data were analyzed qualitatively and descriptively reported. The findings revealed that the principals at the two schools show different results. The principal of elementary school effectively perform in principal-staff relations, students’ relationships, and community and parent relations. Meanwhile, the principal of middle school show effective performance not only in the above three-mentioned aspects but also in organization and building management as well as curriculum and program development.